A prospective study of patient‐reported xerostomia‐related outcomes after parotidectomy. Issue 4 (29th May 2021) - Brodie, Kara D.; Zebolsky, Aaron L.; Ochoa, Edgar; Ha, Patrick K.; Heaton, Chase M.; El‐Sayed, Ivan H.; Ryan, William R.
Abstract: Objective: There is a paucity of data on patient‐reported outcome measures regarding xerostomia after parotidectomy surgery. Although salivary flow rates after parotidectomy have been previously studied, they do not correlate with subjective xerostomia. This study was designed to evaluate if unilateral parotidectomy increases patient‐reported xerostomia. Methods: A prospective cohort of patients undergoing unilateral partial, superficial, or total parotidectomy for benign or low‐grade malignant pathology without postoperative radiation at a tertiary care academic center was studied. We analyzed patient‐reported outcome measures of xerostomia using the Xerostomia Questionnaire (XQ) preoperatively and postoperatively. We compared pre‐ and postoperative cumulative and individual XQ scores using Wilcoxon signed‐rank tests. We stratified patients by the weight in grams (g) of the parotid tissue excised, pathology, smoking status, and xerostomia‐related medication use. Results: Twenty‐two adults with benign or low grade malignant unilateral parotid tumors were included. Postoperative questionnaires were completed at a median of 10.2 months (interquartile range [IQR] 8.6‐11.9) after unilateral parotidectomy. Mean preoperative and postoperative cumulative XQ scores, on a 100‐point scale, with higher scores representing worse symptoms, were 10.33 (95% CI: 4.46‐16.20) and 10.54 (95% CI: 5.10‐15.98), respectively, with a mean change of +0.21 ( p  = 0.472). There were no statistically significant changes in individual XQ symptom scores. Neither type of parotidectomy, resection specimens weighing over 10 g, smoking habits, xerostomia‐related medication use, nor malignant pathology were associated with worse symptom scores. Conclusion: Based on these data, unilateral parotidectomy does not appear to definitely, or at least consistently, increase xerostomia per patient reporting. More extensive parotid resections are not associated with worse symptom scores. These data can help guide preoperative counseling and postoperative expectations for parotidectomy. Level of Evidence: 2b.